Immune Checkpoint Blockade Restores HIV-Specific CD4 T Cell Help for NK Cells - Porichis, Filippos; Hart, Meghan G; Massa, Alexandra; Everett, Holly L; Morou, Antigoni; Richard, Jonathan; Brassard, Nathalie; Veillette, Maxime; Hassan, Muska; Ly, Ngoc Le; Routy, Jean-Pierre; Freeman, Gordon J; et al. (The Journal of immunology (1950), 2018)
Immune exhaustion is an important feature of chronic infections, such as HIV, and a barrier to effective immunity against cancer. This dysfunction is in part controlled by inhibitory immune checkpoints. Blockade of the PD-1 or IL-10 pathways can reinvigorate HIV-specific CD4 T cell function in vitro, as measured by cytokine secretion and proliferative responses upon Ag stimulation. However, whether this restoration of HIV-specific CD4 T cells can improve help to other cell subsets impaired in HIV infection remains to be determined. In this study, we examine a cohort of chronically infected subjects prior to initiation of antiretroviral therapy (ART) and individuals with suppressed viral load on ART. We show that IFN-γ induction in NK cells upon PBMC stimulation by HIV Ag varies inversely with viremia and depends on HIV-specific CD4 T cell help. We demonstrate in both untreated and ART-suppressed individuals that dual PD-1 and IL-10 blockade enhances cytokine secretion of NK cells via restored HIV-specific CD4 T cell function, that soluble factors contribute to these immunotherapeutic effects, and that they depend on IL-2 and IL-12 signaling. Importantly, we show that inhibition of the PD-1 and IL-10 pathways also increases NK degranulation and killing of target cells. This study demonstrates a previously underappreciated relationship between CD4 T cell impairment and NK cell exhaustion in HIV infection, provides a proof of principle that reversal of adaptive immunity exhaustion can improve the innate immune response, and suggests that immune checkpoint modulation that improves CD4/NK cell cooperation can be used as adjuvant therapy in HIV infection.